Pozycjonowanie jako kategoria analizy nauczycielskich narracji autobiograficznych = Positioning as a category of analysis of teachers` autobiographical narratives - Kowalska, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Studies on teachers` identity constitute an essential field in pedeutologic research. Among empirical works undertaking this subject-matter, the research trend using F. Schutze`s methodological concept is clearly distinguishable. This article attempts at familiarizing the reader with a different, drawing on conversational analysis, approach to narrative identity research. The essence of this approach is to introduce the category of positioning into research. Positioning may be a useful tool for the conceptualization and the study of the process of narrative identity constitution.
Keywords: nauczyciele; tożsamość narracyjna; pozycjonowanie; teacher; narrative identity; positioning